Grand concert of secular music by the Beethoven Society at Touro Hall, Wednesday evening, May 30, 1860 (Hartford, CT; printed by Charles Montague, 2020)
Program sponsored by the Beethoven Society of Hartford, CT, with performances of works by Von Bree, Flotow, Balfe, Labitzsky, Rossini, Weber, T. Cooke, Bellini, Mendelssohn, Mozart, Lumbye, and Bishop, conducted by J. G. Barnett, with J. Mahler as leader of orchestra and Geo. E. Whiting, pianist.